Comparative Evaluation of Solanum tuberosum L. and Manihot esculenta Starch as Pharmaceutical Excipients: Assessment by Preformulation Studies - Hasan, Md Mahadi; Rana, Md Sohel; Uddin, Nizam; Rahman, Kazi Jamiur; Chowdhury, Sanchita Sharmin (Bangladesh Pharmaceutical Journal, 2015)
This investigation was aimed at comparing the newly developed starches from two grains; Potato (Solanum tuberosum) and Cassava (Manihot esculenta). The presence of starch in as these grains vary and thus their use as pharmaceutical excipients will depend on the degree of their starch functionality. The organoleptic and physicochemical characteristics such as viscosity, swelling capacity, moisture sorption capacity, pH, flow rate, Carrs index, and Hausners ratio were evaluated. The powders passed the identification and solubility tests as required by the British Pharmacopoeia. Cassava starch showed the least Carrs index, Hausners ratio and moisture sorption capacity but displayed more angle of repose and true density than the potato starch. In contrast, potato starch showed the highest hydration and swelling-capacity. That is why, potato starch could be a better tablet disintegrant compared to cassava starch. The results obtained demonstrated that between the two starches in relation to their flow ability, cassava starch possesses the best flow property. Infrared (IR) spectra of potato and cassava starch with the drug sample (Etoricoxib) were seen to retain the individual peak of potato and cassava starch and the IR spectra showed that there was no interaction of starch with the drug. DOI: http://dx.doi.org/10.3329/bpj.v17i2.22328 Bangladesh Pharmaceutical Journal 17(2): 128-134, 2014